Stockpiling strategic materials : an evaluation of the national program - Mikesell, Raymond Frech (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1986)
The National Defense Stockpile (NDS) has been the subject of many books and articles and thousands of pages of congressional hearings and government reports over the past half-century. This study is based on the author's research on stockpiling supported by the joint Mineral Economics and Policy Program of Pennsylvania State University and Resources for the Future.
Includes bibliographical references..
ne 08/06/2018
Loans
Keywords: Strategic materials; Mineral industries; National security